2009
DOI: 10.1021/ma901765j
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism of β-Phase in PVDF/CNT Composite Prepared by the Sonication Method

Abstract: Two poly(vinylidene fluoride)(PVDF)/carbon nanotube (CNT) composites are prepared by solution sonication and mechanical mixture approaches. It is found that α-phase coexists with β-phase in the composite prepared by sonicating the PVDF/CNT mixture solution, while no β-phase can be observed in the composite prepared from the mechanical mixture route. With the help of the density functional theory calculations, it is explained that a large amount of energy is required for transforming trans−gauche−trans−gauche′ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
204
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(215 citation statements)
references
References 20 publications
11
204
0
Order By: Relevance
“…As demonstrated in the XRD results, it was found that the PVDF-PCNTs nanocomposite films consisted of the -phase and the -phase PVDF. The absorbance bands at 613 cm −1 (CF 2 bending), 763 cm −1 (CF 2 wagging vibration), and 975 cm −1 (CF 2 rocking vibration) were related to the -phase [8]. However, the absorbance bands at 838 cm…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…As demonstrated in the XRD results, it was found that the PVDF-PCNTs nanocomposite films consisted of the -phase and the -phase PVDF. The absorbance bands at 613 cm −1 (CF 2 bending), 763 cm −1 (CF 2 wagging vibration), and 975 cm −1 (CF 2 rocking vibration) were related to the -phase [8]. However, the absorbance bands at 838 cm…”
Section: Resultsmentioning
confidence: 93%
“…In order to demonstrate the transition of PVDF crystalline structures, the pure PVDF and PVDF-MWCNTs composite films are also analyzed; it can be found that three distinctive peaks are observed at three different diffraction angles (2 ): 18.4 ∘ , 19.9 ∘ , and 26.5 ∘ corresponding to (020), (110), and (021) crystal plane from the -phase crystalline structure [8]. When it comes to the PVDF-PCNTs composite films, the peak at 2 = 20.8…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, studies do not agree on the percolation threshold [40][41][42][43][44] since there is no unique value, as it depends on the process conditions, the possible preferred orientation of the CNTs in the matrix, the CNTs type and their characteristics (i.e. AR, surface modification [45][46][47][48]). In the case of a 5 wt% of MWCNT, the conductivity still increases although flexibility and processability of the polymer is lost as reported by Lonjon et al [49] in the case of P(VDF-TrFE) and nickel nanowires.…”
Section: Pani Systemmentioning
confidence: 99%
“…Various methods have been proposed and implemented [11][12][13][14] to increase the β phase content of PVDF films; however high temperature mechanical stretching and high voltage poling using are proved to be efficient and practical [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%